PENGARUH TINGKAT PENDIDIKAN DAN KOMPENSASI TERHADAP PRESTASI KERJA APARATUR SIPIL NEGARA (ASN) PADA DINAS PENDIDIKAN DAN KEBUDAYAN KOTA SERANG - Ubay Haki Ubay Haki; Istikomah Istikomah (LPPM STIA Banten, 2018)
An organization is demanded that the implementation of the duties and functions of the organization be carried out quickly, smoothly and directed so that its implementation runs effectively and efficiently. To be able to maintain the sustainability of an organization, human resources that have superior quality in their fields are needed. In addition, humans resources must also have education in accordance with their position or position. As well as being encouraged with appropriate compensation to achieve good performance resulting in good work performance as well. The purpose of this research is to find out whether there is an influence between the level of education and compensation for work performance. The method used in this research is survey method, with quantitative correlation and regression approaches. The sample of 50 people taken from the State Civil Apparatus (ASN) in the Serang City Education and Culture Office. Data processing method uses multiple regression analysis. The results showed that the level of education and compensation simultaneously or partially had a significant effect on employee work performance. From the results of the determination coefficient test, the determination the coefficient value is 0.351.